أثر تطبيقات الذكاء الاصطناعي على إدارة الموارد البشرية: الفرص، التحديات، والتحول المستقبلي (Comprehensive Journal of Science, 2025)
Over the past two decades, the world has witnessed an unprecedented development in artificial intelligence technologies, the effects of which have spread to various economic and social sectors. The field of human resources management is one of the most prominent areas that have begun to invest in these technologies because of the wide opportunities they provide to improve efficiency, increase the speed of decision-making, and enhance the employee experience. However, at the same time, the integration of these applications raises challenges related to privacy, ethics, and job substitution, which calls for in-depth thinking about the future of human resources in the era of digital transformation.This research aims to study the impact of artificial intelligence applications in human resources management by focusing on three main axes: available opportunities, current challenges, and expected future transformations. The research was based on a review of modern scientific literature, as well as an analysis of some international experiences in this field. The research concluded that artificial intelligence represents a promising strategic tool if used in a rational legislative and ethical framework, which opens up new horizons for human resources departments to go beyond their traditional role and become a strategic partner in corporate decision-making.
Keywords: Artificial intelligence, human resource management, digital transformation, ethical challenges.